The classification of knowledge in Islam: a descriptive analysis - Sulaiman, Kabuye Uthman (IIUM Press, 2024)
The aim of this work is to describe the various types of knowledge in Islam. Islam places a greater emphasis on knowledge acquisition, dissemination, application, and preservation than any other religion. The Arabic term ‘ilm (knowledge), is regarded as one of the most frequently mentioned terms in the Qur’ān, whether as a noun, verb, or adjective. This work uses a descriptive analysis method based on desk research and draws on primary Islamic sources, namely, the Qur’ān and Ḥadīth, as well as secondary works on knowledge. The focus of the study is on the classification of knowledge, such as al-‘Ilm al-Mutlaq (Absolute knowledge), al-‘Ilm al-Muqayyad (limited knowledge), God-given knowledge, etc., including its importance based on its sources, acquisition, and application. The findings of this work show that knowledge is acquired through various sources that determine its definition, classification, interpretation, and application